2021
DOI: 10.2298/vsp200229043v
|View full text |Cite
|
Sign up to set email alerts
|

High number of CD14+B7H4+ monocytes is significantly associated with increased concentrations of IL-4, IL-13, IL-10, and TGF-β1 in tumor microcirculation of lung carcinoma

Abstract: Introduction. Lung cancer is one of leading causes of mortality. Disease progression and advanced disease are characterized with unprotective immune response due to M2 macrophage polarization, MDSC activity, cytokine imbalance and regulatory T lymphocyte activity. Material and methods. We have investigated principal Th1/Th2 cytokines and CD14 + B7H4 + monocyte number in blood and tumor microcirculation samples of 41 lung cancer patients (III and IV clinical stage) and 30 controls. Aim. To investigate associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Out of all the articles included in the meta-analysis [27][28][29][30][31], only one study [27] reported a significantly lower level of IL-6, while 20 studies [28, 29, 39, 45-52, 54, 55, 58-62, 65, 66] found a higher level of IL-6 in LC cases than in HCs. The remaining studies [30,31,53,56,57,64] did not find any significant difference between the two groups. Some studies [57,58,67] showed that serum IL-6 was linked to anxiety and depression in LC cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of all the articles included in the meta-analysis [27][28][29][30][31], only one study [27] reported a significantly lower level of IL-6, while 20 studies [28, 29, 39, 45-52, 54, 55, 58-62, 65, 66] found a higher level of IL-6 in LC cases than in HCs. The remaining studies [30,31,53,56,57,64] did not find any significant difference between the two groups. Some studies [57,58,67] showed that serum IL-6 was linked to anxiety and depression in LC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight studies [27][28][29][30][31] were published from 1996 to 2022 (Table I). Among all studies, eleven studies were reported in Caucasians, fourteen in Asians, and three in mixed ethnicities.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation